Comparison of percutaneous device closure versus surgical closure of peri‐membranous ventricular septal defects: A systematic review and meta‐analysis. Issue 6 (10th August 2015) - Saurav, Alok; Kaushik, Manu; Mahesh Alla, Venkata; White, Michael D.; Satpathy, Ruby; Lanspa, Thomas; Mooss, Aryan N.; DelCore, Michael G.
Abstract : Background: While percutaneous device closure (PDC) is a first‐line therapy for isolated muscular ventricular septal defects (mVSD), surgery is still the preferred approach for peri‐membranous ventricular septal defects (pmVSD). Objective: We sought to compare the outcomes of percutaneous versus open surgical closure of pmVSDs. Methods: PubMed, Cochrane Library, and Web of Science databases were searched through October 15, 2014 for English language studies comparing outcomes of PDC with surgical closure of pmVSDs. Study quality, publication bias, and heterogeneity were assessed. A meta‐analysis of selected studies was performed using a random effects model. Comparison was done for early (<1 month) safety and efficacy outcomes. Results: Seven studies with a total of 3, 134 patients (PDC = 1, 312, surgery = 1, 822) were identified. Patients in the PDC group were older than those treated surgically (mean age 12.2 vs. 5.5 years, respectively). In six out of seven studies, the mean VSD size was found to be comparable between the treatment arms (PDC 4.9 mm vs. surgery 6.0 mm). Males represented 52% of patients in either group. Follow‐up ranged from 5 to 42 months. No significant differences were observed between PDC vs. surgery in terms of procedural success rate [relative risk (RR): 1.00, confidence interval (CI): 0.99–1.00; P  = 0.67]. Combined safety end points for major complications (early death/reoperation/permanent pacemaker) were similar in both groups (RR: 0.55, CI: 0.23–1.35; P  = 0.19) as were as other outcomes like post‐procedure significant residual shunt (RR: 0.69, CI: 0.29–1.68; P  = 0.41), significant valvular (aortic/tricuspid) regurgitation (RR: 0.70, CI: 0.26–1.86; P  = 0.47), and advanced heart block (RR: 0.99, CI: 0.46–2.14; P  = 0.98). The need for blood transfusion (RR: 0.02, CI: 0.00–0.05; P  < 0.001) and duration of hospital stay [standard mean difference (SMD) −2.17 days, CI: −3.12 to −1.23; P  < 0.001] were significantly reduced in the PDC group. Conclusion: Percutaneous closure of pmVSD when performed in a selected subgroup of patients is associated with similar procedural success rate without increased risk of significant valvular regurgitation or heart block when compared with surgical closure. © 2015 Wiley Periodicals, Inc.